Peran Health Technology Assesment (HTA) Dalam Pelayanan Kesehatan Di Rumah Sakit - Wahyuni, Sri; Vidyan, Anggy; Nurfarahin, Nurfarahin; Hartono, Budi (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
The Indonesian Ministry of Health has carried out health transformation through six pillars, one of which is the pillar of health financing system transformation which is the leading sector of the Health Development Policy Agency (BKPK). The fourth pillar of health transformation is carried out to ensure adequate, fair, effective and efficient health financing. The program carried out for the allocation stage is the improvement of Health Technology Assessment (HTA) to ensure quality and cost control. The purpose of this study is to show that HTA is the most appropriate way to assess both in terms of management, technology, patients and economic losses and can be used by the hospital to make improvements in overcoming problems in the hospital. This study uses the Literature review method. Hospital-based Health Technology Assessment (HTA) developed to answer the needs of hospitals in decision making by not ignoring the hospital context, resulting in evidence-based policies. Hospital based HTA is also a guideline for decision making in the selection of health technology in Indonesia.